2019
DOI: 10.2134/jeq2019.03.0128
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Parameters Affecting the Concentration of Iodine in New Zealand Pasture

Abstract: Iodine (I) is an essential trace element commonly deficient in agricultural systems. Whereas there is much information on I in food crops, there is a lacuna of knowledge on the environmental factors that affect pasture I concentrations. We aimed to identify the most important environmental factors affecting the concentration of I in New Zealand pastures, and the consequences to agricultural systems. Soil and pastoral samples were collected throughout the country and analyzed for I and other elements. The soils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…These higher concentrations may be due to the experimental farm being on the banks of the Ölfusá River, a body of water that carries glacial water (commonly rich in I) and at close proximity to the sea (~20 km) [ 78 , 79 ]. Coastal areas have more I in the soil and subsequently produce forage that may also have higher I concentrations [ 80 ]. The potential effect of Icelandic cow genetics may not be excluded as it is known that breed can also be a driver for milk I concentrations [ 75 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…These higher concentrations may be due to the experimental farm being on the banks of the Ölfusá River, a body of water that carries glacial water (commonly rich in I) and at close proximity to the sea (~20 km) [ 78 , 79 ]. Coastal areas have more I in the soil and subsequently produce forage that may also have higher I concentrations [ 80 ]. The potential effect of Icelandic cow genetics may not be excluded as it is known that breed can also be a driver for milk I concentrations [ 75 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The site is located about 1 km east of the coast and strong westerly winds are common in this area, increasing sea spray [65]. It has been demonstrated that sea spray can affect pasture Na concentrations up to 50 km inland [66]. Although Na is not an essential element for most terrestrial plants and can be directly toxic, with woody species being most susceptible [67,68], there were no visual signs indicating such toxicity in K. robusta and L. scoparium.…”
Section: Plant Growth and Chemistrymentioning
confidence: 99%
“…Unlike most other elements, weathering of rocks and sediments is not a major source of I for the soil–plant system (Johnson, 2003 ). Only a small proportion of the soil I available to plants is derived directly from rock weathering (Fuge & Johnson, 2015 ; Jensen et al, 2019 ). In contrast, oceans are major reservoirs of I (Fuge & Johnson, 2015 ; Manousou et al, 2019 ; Medrano-Macías et al, 2016 ) and volatilisation from ocean water and movement through the atmosphere plays an essential role in I cycling through the environment and the biosphere (Johnson, 2003 ; Medrano-Macías et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, oceans are major reservoirs of I (Fuge & Johnson, 2015;Manousou et al, 2019;Medrano-Macías et al, 2016) and volatilisation from ocean water and movement through the atmosphere plays an essential role in I cycling through the environment and the biosphere (Johnson, 2003;Medrano-Macías et al, 2016). Thus, I input from the atmosphere, as dry or wet precipitation, often contributes greatly to soil and plant I (Bowley et al, 2019;Fuge & Johnson, 1986;Jensen et al, 2019;Johnson, 2003). It is recognised that I concentrations are greater in coastal areas compared to inland and mountainous regions located away from coasts (Bowley et al, 2016;Fuge & Johnson, 2015;Humphrey et al, 2018).…”
mentioning
confidence: 99%